Breathe In, Breathe Out: Metabolic Regulation of Lung Macrophages in Host Defense Against Bacterial Infection - Andrews, J. Tucker; Voth, Daniel E.; Huang, Stanley Ching-Cheng; Huang, Lu (Frontiers in Cellular and Infection Microbiology, 2022)
Lung macrophages are substantially distinct from other tissue-resident macrophages. They act as frontier sentinels of the alveolar-blood interface and are constantly exposed to various pathogens. Additionally, they precisely regulate immune responses under homeostatic and pathological conditions to curtail tissue damage while containing respiratory infections. As a highly heterogeneous population, the phenotypes and functions of lung macrophages with differing developmental ontogenies are linked to both intrinsic and extrinsic metabolic processes. Importantly, targeting these metabolic pathways greatly impacts macrophage functions, which in turn leads to different disease outcomes in the lung. In this review, we will discuss underlying metabolic regulation of lung macrophage subsets and how metabolic circuits, together with epigenetic modifications, dictate lung macrophage function during bacterial infection.